Analisis Daya Serap Suara Material Berbasis Polyester Staple Fibre Untuk Karpet Lantai Kendaraan - Joko Sumbogo, Yuliarto; Ardiansyah, Dimas; Suparno, Joko; Riski, Kautzar; Andri W.H, Dwi (Politeknik Negeri Cilacap, 2023)
This research studies about the ability of the acoustic properties or absorption of the vehicle floor carpet material which consists of several forming components, with an experimental method using the tube impedance method. The components of this car floor carpet material consist of a skin section which includes a surface made of polyester staple fiber plastic fiber, binders made of latex SBR material, backing made of Polyethylene (PE) powder and the under layer made of Polyester Fiber material (PET) Silencer. The carpet material for the vehicle floor was made into three samples to determine the average of sound absorption coefficient. The sound absorption coefficient was obtained from testing the flat test sample using the ASTM E1050-98 tube impedance method. The use of Polyethylene (PE) powder as a backing for floor mats has a sound absorption coefficient with a rating of B (above 0.8) at a frequency of 3,000 Hz. While the sound absorption coefficient reaches the highest point of 0.99 at a frequency of 3,000 Hz. This is because the backing with Polyethylene (PE) powder material has porous holes. The micro surface is used as a layer of air space so that it can effectively reduce and increase the absorption of sound that occurs inside the vehicle when driving. The sound absorption coefficient of vehicle floor carpet increases significantly at low frequencies and slightly decreases at high frequencies